The role of hepatic stellate cells in the regulation of T-cell function and the promotion of hepatocellular carcinoma - ZHAO, WENXIU (D.A. Spandidos, 2012)
Hepatic stellate cells (HSCs) have immunosuppressive abilities and may be responsible for the occurrence and development of hepatocellular carcinoma (HCC). However, the mechanisms through which HSCs affect T-cell-mediated immune responses remain unclear. The aim of this study was to elucidate these mechanisms. We examined the effect of HSCs on T-cell proliferation and apoptosis, regulatory T cells (Treg cells) and T-cell-mediated cytotoxicity using mixed leukocyte reactions (MLRs). Furthermore, we examined the cytokines present in the supernatant and the effect of this supernatant on the proliferation and migration of cancer cells. Finally, we examined the effect of HSCs on HCC cells in vivo. We found that activated HSCs induced T-cell hyporesponsiveness, accelerated activated T-cell apoptosis, increased the number of Treg cells and inhibited T-cell-mediated cytotoxicity. HSCs also enhanced the expression of some cytokines and promoted the proliferation and migration of cancer cells. Furthermore, activated HSCs were able to induce HCC proliferation and Treg cells expansion in vivo. Activated HSCs may induce T cell anergy, thereby facilitating the immunologic escape of HCC cells.